Comparison of fully wettable RPLC stationary phases for LC‐MS‐based cellular metabolomics. Issue 18 (1st August 2017) - Si‐Hung, Le; Causon, Tim J.; Hann, Stephan
Abstract: Reversed‐phase LC combined with high‐resolution mass spectrometry (HRMS) is one of the most popular methods for cellular metabolomics studies. Due to the difficulties in analyzing a wide range of polarities encountered in the metabolome, 100%‐wettable reversed‐phase materials are frequently used to maximize metabolome coverage within a single analysis. Packed with silica‐based sub‐3 μm diameter particles, these columns allow high separation efficiency and offer a reasonable compromise for metabolome coverage within a single analysis. While direct performance comparison can be made using classical chromatographic characterization approaches, a comprehensive assessment of the column's performance for cellular metabolomics requires use of a full LC‐HRMS workflow in order to reflect realistic study conditions used for cellular metabolomics. In this study, a comparison of several reversed‐phase LC columns for metabolome analysis using such a dedicated workflow is presented. All columns were tested under the same analytical conditions on an LC‐TOF‐MS platform using a variety of authentic metabolite standards and biotechnologically relevant yeast cell extracts. Data on total workflow performance including retention behavior, peak capacity, coverage, and molecular feature extraction repeatability from these columns are presented with consideration for both nontargeted screening and differential metabolomics workflows using authentic standards and Pichia pastoris cell extract samples.